Palestinian Refugees in Lebanon: Is the Camp a Space of Exception? - Leonardo Schiocchet (Mashriq & Mahjar, 2021)
This article engages the Agamben-Agier perspective on refugee camps, which has become dominant in the last few years but has received little critical analysis. Both Giorgio Agamben and Michel Agier at times define the refugee camp in relation to broader scenarios. While Agamben thinks of the camp as a way to define the modern nation state and law, Agier often digresses from the camp with the city in mind. While the work of both teaches us a great deal about the nature of the camp, discussing some of their limitations is essential even to fully develop their own potential. This article aims at contrasting key elements of the Agamben-Agier perspective to my own experience in Palestinian refugee camps in Lebanon. Three main questions underpin this paper: Is a refugee camp indeed a space of exception? Should we understand the refugee camps in their symbolic and practical continuity or discontinuity to the urban space? Should we consider the camp as having the same properties of the “city” in Agier’s sense?